Dados, informação e conhecimento enquanto elementos de compreensão do universo conceitual da ciência da informação: contribuições teóricas - Semidão, Rafael Aparecido Moron [UNESP] (2014)
It examines the concepts of data, information and knowledge and metaphorical relationships between them as forms of conceptual articulation in Information Science. Undertake a interpretation of the epistemological dynamic of Information Science for reference to conceptual analysis aimed to be expressive of a structure that combines epistemological, theoretical, historical and pragmatic elements. Adopts a bibliographical and interpretive approach and taking a corpus as a set of specialized dictionaries and manuals. Six explanatory metaphors of the links between the concepts of data, information and knowledge were identified, with the most frequent among them had a cognitive intonation, which made to seek to reflect on the origins and possible influences of a cognitive analogy as a paradigm based to the conceptual joints in Information Science. We identified the origin and the influence of a cognitive analogy in Information Science with the emergence of called Cognitive Sciences on the U.S. scientific scenario.